EVOLVING NOTIONS OF PUBLIC INTEREST: A NEW PERSPECTIVE ON LAND ACQUISITION IN INDONESIA - Amal, Bakhrul; Yusriadi, Yusriadi; Silviana, Ana (UI Scholars Hub, 2024)
Indonesia relating to land issues. The meaning of public interest in land acquisition which is expected to be able to help realize justice, prosperity and welfare for the community turns out that in its implementation it actually causes conflict because it is not in accordance with the principles of balance and justice. The problems that the research tries to answer are: (1) What is meant by public interest according to the applicable laws and regulations? (2) How is the reconstruction of the meaning of public interest in land acquisition for development in the public interest based on the principles of balance and justice? To answer this problem, the paradigm used in this research is the constructivism paradigm, supported by the theory of the rule of law, the theory of legal interpretation, and the theory of corrective justice. The methodology in this research uses sociolegal methodology. From this research, it was found that the meaning of public interest in the Basic Agrarian Law apparently changed inconsistently in the derivative regulations that followed. The correct meaning of public interest is the interest of the nation, state, and society, which continues to pay attention to individual interests and must be realized jointly by the central or regional government and the community and used as much as possible for prosperity, justice, and happiness for society as a whole. The recommendation from this research is the need for consistency in the formation of laws and regulations in accordance with the principles of the rule of law. In addition, the government is expected to pay attention to the principles of balance and justice in the land acquisition process for development in the public interest. The current meaning of public interest needs to be reconstructed according to the objectives of UUPA.